Analisis Kepuasan Pengguna Trans Banyumas Terhadap Layanan Transportasi Berbasis Smart Mobility Menggunakan Metode CSI - Izza Aulia, Rofiul; Rizal Aprianto; Azel Rizal Jovian (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2025)
The development of mobility in Banyumas Regency shows its own challenges in the effort to build an efficient and environmentally friendly transportation system. The high dependence of people on private vehicles has an impact on increasing congestion and decreasing air quality. As a response to these conditions, Trans Banyumas is present as a public transportation service based on smart mobility with the support of digital technology and a cashless payment system. This study was conducted to evaluate the parameters of user satisfaction with Trans Banyumas services. Data collection was conducted by survey using a questionnaire covering four aspects of service, namely accessibility, information technology, security, and sustainability. The Customer Satisfaction Index (CSI) method was used to determine the extent to which services have met user expectations. Of the 100 respondents involved, a CSI value of 78.34% was obtained, which means that in general users feel satisfied with the Trans Banyumas service. This finding indicates that the implementation of smart mobility in Trans Banyumas has been running quite well. However, strengthening is still needed in several aspects, such as the accuracy of arrival time information and expansion of service coverage.